Do Social Workers Apply "Love Thy Neighbor as Thyself" to Gay, Lesbian, Bisexual, and Transpersons in the South?. Issue 9 (1st September 2016) - Lennon-Dearing, Robin; Delavega, Elena
ABSTRACT: Across the United States there has been a spate of legislative bills and initiatives that blatantly stigmatize and discriminate against the lesbian, gay, bisexual, and transgender (LGBT) community. This study was a cross-sectional, exploratory survey designed to measure the attitudes, perceptions, and behaviors of Tennessee social workers and future social workers toward the LGBT population and toward proposed discriminatory legislation. A 3-way factorial ANOVA investigated the effects of political affiliation, religious affiliation, and social contact on the dependent measures. Significant main effects were found. Self-reported political affiliation was found to be the most important factor predicting LGBT acceptance and LGBT respect among this sample.